ANALISIS KEUNGGULAN KOMPETITIF SEKTORAL UNTUK PENGEMBANGAN EKONOMI LOKAL KABUPATEN PURBALINGGA - Yesi Nuralfiani; Rahmat Alhakim (INUMIYA: Jurnal Ekonomi Pembangunan, 2023)
This research aims to examine the sectoral competitive advantages of the local economy of Purbalingga Regency based on their growth and contribution, in order to obtain an overview of basic, non-basic sectors and potential sectors that have competitive advantages in order to develop local economic potential. The approach used is to use quantitative descriptive using analytical tools consisting of; 1) Klassen Typology Analysis; 2) LQ Analysis; 3) DLQ analysis; 4) Shift Share Analysis; 5) Growth Ratio Model Analysis and 6) Overlay. The data used are PDRB ADHK 2010 2016-2020 Purbalingga Regency and PDRB Central Java Province. The research results show that the agriculture, forestry and fisheries sectors are consistently the three leading sectors based on Location Quotient (LQ), Dynamic Location Quotient (DLQ) analysis. The results of the Shift Share Analysis show that the Purbalingga economy generally has a positive trend except in the proportional analysis where the industrial mix puts pressure on the agriculture, forestry and fisheries sectors; mining and quarrying sector; processing industry sector; transportation and warehousing sectors and government administration, defense and mandatory social security sectors. Further MRP analysis shows that the Purbalingga Regency economic sector has 3 (three) sectors with positive RPr and RPs values. These sectors are the agriculture, forestry and fisheries sectors; electricity and gas procurement sector; waste, waste and recycling management sector. The results of the overlay analysis show that the Purbalingga Regency economic sector has a fast pace and contribution at both the Regency and Central Java Province levels. These sectors are the water supply, waste management, waste and recycling sectors. Based on research results which show that the economic structure is still oriented towards the primary sector with a good growth rate and contribution to the economy, it is hoped that the Purbalingga Regency government can improve its performance in the field of community (farmer) empowerment in this sector, through training, technical guidance and primarily encouraging agricultural institutions so that they can increase competitiveness on a regional and national scale